2017
DOI: 10.18632/oncotarget.23322
|View full text |Cite
|
Sign up to set email alerts
|

Novel cooperative pathway of c-Myc and Furin, a pro-protein convertase, in cell proliferation as a therapeutic target in ovarian cancers

Abstract: c-Myc is a master regulator of various oncogenic functions in many types of human cancers. However, direct c-Myc-targeted therapy has not been successful in the clinic. Here, we explored a novel therapeutic target, which shows synthetic lethality in c-Myc-driven ovarian cancers, and examined the molecular mechanism of the synthetic lethal interaction. By high throughput siRNA screening with a library of 6,550 genes, Furin, a pro-protein convertase, was identified as the top hit gene. Furin inhibition by siRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…This discovery was consistent with our finding that FURIN was a negative indicator for CC. Furthermore, it was reported that FURIN could predict survival in ovarian cancer 31 and might be seemed as a prognostic marker and therapeutic target for cancer 32‐34 . These studies might provide further evidence for our findings that the five genes were associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…This discovery was consistent with our finding that FURIN was a negative indicator for CC. Furthermore, it was reported that FURIN could predict survival in ovarian cancer 31 and might be seemed as a prognostic marker and therapeutic target for cancer 32‐34 . These studies might provide further evidence for our findings that the five genes were associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 79%
“…Among them, two pc-genes, FURIN and NFE2, and two lncRNAs, LINC02432 and MIR3945HG, were further interrogated at genomic and transcriptomic level, confirming the efficiency of the pgRNA DECKO system in knocking out protein and lncRNA expression. FURIN and NFE2 have been previously involved in myeloid branch differentiation (18)(19)(20) and MIR3945HG has been found overexpressed in tuberculosis infected human macrophages (21). This confirms that, with our system, we have indeed been able to specifically uncover both pc-genes and lncRNAs involved in blood differentiation.…”
Section: Introductionsupporting
confidence: 84%
“…This protein is a ubiquitously expressed serine protease enzyme that processes substrates like cytokines, hormones, receptors and growth factors like TGFB1, which controls proliferation and differentiation in many cell types (41); and has been involved in tumour progression, representing an interesting therapeutic target. FURIN has been also related to monocyte/macrophage migration and proliferation, being also an inhibitor of apoptosis (19,20). Actually, the expression pattern of FURIN suggests that it is involved in the last steps of macrophage lineage determination, consistent with its role in macrophage motility.…”
Section: Discussionmentioning
confidence: 92%
“…It controls proliferation and differentiation in many cell types [46] and has been involved in tumor progression, representing an interesting therapeutic target. FURIN has been also related to monocyte/macrophage migration and proliferation, being also an inhibitor of apoptosis [29,31]. Actually, the expression pattern of FURIN suggests that it is involved in the last steps of macrophage lineage determination, consistent with its role in macrophage motility.…”
Section: Discussionmentioning
confidence: 92%
“…Among them, two pc-genes, FURIN and NFE2, and two lncRNAs, LINC02432 and MIR3945HG, were further interrogated at genomic and transcriptomic level, confirming the efficiency of the pgRNA DECKO system in knocking out protein and lncRNA expression. The fact that some of the identified candidates have been previously associated with blood differentiation and response to infection [28][29][30][31] confirms that this system is suitable to specifically uncover both pc-genes and lncRNAs involved in such processes, while it provides new potential candidates for further characterization. In the case of the lncRNAs, the knock down experiments indicated that the lncRNAs transcripts may not be directly involved in the regulation of transdifferentiation, but the impact of the CRISPR-Cas9 interference in the process may be mediated by enhancer regions at the targeted loci.…”
Section: Introductionmentioning
confidence: 77%